Social protection programmes: narratives of Nigerian women and anti-trafficking practitioners in Italy - Semperbon, Michela (Routledge advances in sociology, 2023)
"This book deals with social protection programmes targeted to people trafficked for the scope of sexual exploitation. It provides empirical evidence on the N.A.Ve programme, in the north-eastern Italian Veneto Region, and its evolution. It elaborates on the programme by narrating the subjective experiences of practitioners and of a specific group of beneficiaries: young Nigerian women - some in transition towards the majority age. The book builds on qualitative research, including a long institutional ethnographic research and semi-structured interviews carried out in the period 2019-2021, before and during the Covid-19 pandemic. It takes an intersectional, social work and humanitarian governance perspective to examine the multiple dimensions of vulnerability (age, gender, geographical origin, type of exploitation) characterising trafficked and sexually exploited Nigerian women. It draws attention to the precariousness of protection trajectories, but also on the agency of these women, by building on the autonomy of migration approach, while shedding light on the temporal tensions between biographical and institutional times. Calling for greater space for women's voices and for their involvement in the co-development of protection programmes, this book will appeal to scholars of sociology, anthropology, social work and politics, as well as to practitioners and policymakers interested in migration and trafficking"--